Making implementation science more efficient: capitalizing on opportunities beyond the field - Wensing, Michel; Wilson, Paul (Implementation science, 2023)
Implementation researchers often find themselves as research partners in practice improvement projects, clinical trials or other applied health studies. The implementation science component in these projects can be described as supportive, descriptive or explanatory. This commentary reflects on the potential contributions of such projects to implementation science. They may provide evidence on implementation strategies, so it is essential to identify and evaluate these separately from the clinical and preventive interventions of interest. The use of theory on implementation processes and associated factors can contribute to knowledge accumulation, particularly if the focus is on what actually gets implemented when, why and how. The development and validation of relevant measures is a third potential contribution to implementation science. Although not all issues in implementation science can be addressed in this way, capitalization on the opportunities beyond the field can contribute to implementation science.